The chemical composition and toxicological effects of fine particulate matter (PM2.5) emitted from different cooking styles. (1st November 2021) - Bandowe, Benjamin A. Musa; Lui, K.H.; Jones, Timothy; BéruBé, Kelly; Adams, Rachel; Niu, Xinyi; Wei, Chong; Cao, Jun-Ji; Lee, S.C.; Chuang, Hsiao-Chi; Ho, K.F.
Abstract: The mass, chemical composition and toxicological properties of fine particulates (PM2.5 ) emitted from cooking activities in three Hong Kong based restaurants and two simulated cooking experiments were characterized. Extracts from the PM2.5 samples elicited significant biological activities [cell viability, generation of reactive oxygen species (ROS), DNA damage and inflammation effect (TNF-α)] in a dose-dependent manner. The composition of PAHs, oxygenated PAHs (OPAHs) and azaarenes (AZAs) mixtures differed between samples. The concentration ranges of the Σ30PAHs, Σ17OPAHs and Σ4AZAs and Σ7Carbonyls in the samples were 9627–23, 452 pg m −3, 503–3700 pg m −3, 33–263 pg m −3 and 158 – 5328 ng m −3, respectively. Cell viability caused by extracts from the samples was positively correlated to the concentration of benzo[a]anthracene, indeno[1, 2, 3-cd]pyrene and 1, 4-naphthoquinone in the PM2.5 extracts. Cellular ROS production (upon exposure to extracts) was positively correlated with the concentrations of PM2.5, decaldehyde, acridine, Σ17OPAHs and 7 individual OPAHs. TNF-α showed significant positive correlations with the concentrations of most chemical species (elemental carbon, 16 individual PAHs including benzo[a]pyrene, Σ30PAHs, SO4 2−, Ca 2+, Ca, Na, K, Ti, Cr, Mn, Fe, Cu and Zn). The concentrations of Al, Ti, Mn, Σ30PAHs and 8 individual PAHs including benzo[a]pyrene in the samples were positively correlated with DNA damage caused by extracts from the samples. This study demonstrates that inhalation of PM2.5 emitted from cooking could result in adverse human health effects. Graphical abstract: Image 1 Highlights: Cooking PM2.5 emissions elicited significant bioreactivity in dose-dependent manner. Cantonese cooking style emitted highest PM2.5 and chemical species concentrations. Positive significant correlations showed between PM2.5 /OPAHs and ROS. Majority of high molecular weight PAHs showed strong correlations with TNF-α. Benzo[a]pyrene demonstrated significant positive correlation against DNA damage.